2017
DOI: 10.3390/app7101029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adhesion and Hysteresis Friction of Rubber–Pavement System

Abstract: Tire-pavement friction is a key component in road safety. Adhesion and hysteresis are the two main mechanisms that affect the friction between rubber tires and pavements. This study experimentally examined the relationship between rubber-pavement adhesion and friction. The adhesive bond energy between rubber and pavement surfaces was calculated by measuring the surface energy components of rubber and aggregates. The friction was measured in the laboratory using a dynamic friction tester. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…This sounds normal because tyre becomes softer due to its viscoelastic nature. This remark is in accordance with existing related studies on this subject area [1,27,41,42]. The drop in BPN (from 10 • C to 30 • C) which is around 35% for H D , 25% for H B and H E as temperature increases is beyond the standard error of the measurements which is around 3% to 0.5% and presented in the form of standard error bars.…”
Section: Temperature Effect Resultssupporting
confidence: 92%
“…This sounds normal because tyre becomes softer due to its viscoelastic nature. This remark is in accordance with existing related studies on this subject area [1,27,41,42]. The drop in BPN (from 10 • C to 30 • C) which is around 35% for H D , 25% for H B and H E as temperature increases is beyond the standard error of the measurements which is around 3% to 0.5% and presented in the form of standard error bars.…”
Section: Temperature Effect Resultssupporting
confidence: 92%
“…As reported by Al-Assi and Kassem [1] that rubber generates three different forms of friction which are adhesion, deformation and wear. They also stated that the bulk deformation due to hysteresis causes energy losses as rubber slides over the rough surface.…”
Section: Fig 3 Track Chain With Rubber Pads Adnan -Malaysian Armourmentioning
confidence: 90%
“…It is also possibly due to the shear load resulting from the relative movement of the blocks and the temperature rise due to the hysteresis of these loads. In this case, it was possibly observed that the rubber bush was subjected to hysteresis friction that is caused by the energy dissipation due to internal material damping during the deformation process [1,14]. The deformed part occurs during the sliding of a rubber element across the rough surface.…”
Section: Adnan Malaysian Armoured Vehicle Track Shoementioning
confidence: 99%
See 1 more Smart Citation
“…Changes in asphalt adhesion are caused by the surface's micro-texture (0.1 to 0.5 mm), which is an aggregate composition related property, as the aggregate ability to retain the roughness against the traffic polishing action controls the rate of decrease in adhesion. Hysteresis is the lagging of peak deformation behind peak load, occurring to the tire after passing across asperities of rough surface, caused by the asphalt's macro texture (0.5 to 50 mm), created by cracks and fractures in the asphalt [7].…”
Section: Introductionmentioning
confidence: 99%